SYSTEMIC FAILURES IN PROMOTING LEGAL CULTURE OF INTELLECTUAL PROPERTY RIGHTS AMONG INDONESIA’S CREATIVE ECONOMY ACTORS - Dewandira Darruning Sripradnya Rahmaidha; Adi Sulistiyono; Ayub Torry Satrio Kusumo; Sannia Aziz (Indonesia Private Law Review, 2025)
The creative economy (CE) is a vital driver of national economic growth, yet awareness of Intellectual Property Rights (IPR) among Creative Economy Actors (CE Actors) remains low, with many failing to protect, register, or own IPR. This weak legal culture poses a major barrier to effective IPR protection. This research analyzes the factors behind the government’s failure to foster an IPR legal culture and formulates strategies to strengthen awareness and ownership among CE Actors. Using a socio-legal approach that combines doctrinal legal analysis with empirical investigation, the research identifies systemic obstacles, including inconsistent presidential commitment, the absence of operational frameworks at subnational levels, weak professionalism within the legal bureaucracy, and the lack of IPR and creative economy education. To address these challenges, the government must establish firm and sustained presidential commitment, enact comprehensive implementing regulations, set professionalism standards for relevant bureaucracies, reinforce both internal and external legal culture, and integrate IPR and creative economy content into educational curricula. Coordinated action on these fronts is essential to increase IPR ownership, strengthen legal protection, and support the sustainable growth of Indonesia’s creative economy.